Enhancing mental health support for international students: A digital framework for holistic well-being in higher education - Mahmoud Elkhodr; Ergun Gide; Nishant Pandey (STEM Education)
Mental health issues among students in Australia, particularly international students, remain a significant concern in higher education. We investigated the factors contributing to the ineffectiveness of current mental health services and proposed an innovative digital solution to address these persistent challenges. We introduced a formalized 'Well-being Assistive Technology Framework' designed to tackle key issues students face, including social isolation, financial difficulties, and language barriers. These challenges, while exacerbated during the COVID-19 pandemic, continue to impact student well-being in the post-pandemic era. Based on this framework, a community-based mental health networking mobile application prototype was developed. The app aims to combat mental health issues by facilitating peer support, increasing service awareness, and overcoming language and cultural barriers. It provides a holistic approach to student well-being, incorporating features for quick access support, financial wellness, cultural integration, self-care, self-assessment, legal rights information, and community engagement. Future works involve user-based validation of the developed mobile app to assess its efficacy.